The combination of bacteriophage therapy and antibiotic therapy - Sakib, Sadman; Shounak, Samiha Kamal (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.